ISO 9000 quality management systems : guidelines for enterprises in developing countries (ITC GenevaCH, 1996)
Presents methodology for implementing the elements of ISO 9000 quality management system, with particular reference to small and medium-sized enterprises in developing countries. Provides guidance on preparing such enterprises for third-party certification processes.
DC